2023
DOI: 10.3390/su15032328
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Five-Extraction Technologies’ Environmental Impact on the Polyphenols Production from Moringa oleifera Leaves Using the Life Cycle Assessment Tool Based on ISO 14040

Abstract: The present study examines, compares, and documents the environmental impact of five extraction techniques through Life Cycle Assessment (LCA). The material used was Moringa oleifera freeze-dried leaves and the assessment was based on their polyphenol content Three out of the five examined techniques are referred to in the literature as “green” techniques, namely Pulsed Electric Field (PEF), Microwave-Assisted Extraction (MAE), and Ultrasound-Assisted Extraction (UAE). The other two examined were conventional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…Differences in the various components of LCA studies (such as functional units, system boundaries, laboratory or industrial scale and impact assessment methods) will be considered for comparing the presented results with other studies. However, several studies show differences between traditional extraction methods and green ones, with the latter being more e cient and environmentally friendly (García-García et al, 2019;Pappas et al, 2023). In agreement with the results of this work,Wang et al (2015) reported that ultrasound-assisted heating extraction was an e cient and economical method to obtain higher pectin yields at lower temperatures and shorter extraction times than CHE from grapefruit peel.…”
supporting
confidence: 86%
“…Differences in the various components of LCA studies (such as functional units, system boundaries, laboratory or industrial scale and impact assessment methods) will be considered for comparing the presented results with other studies. However, several studies show differences between traditional extraction methods and green ones, with the latter being more e cient and environmentally friendly (García-García et al, 2019;Pappas et al, 2023). In agreement with the results of this work,Wang et al (2015) reported that ultrasound-assisted heating extraction was an e cient and economical method to obtain higher pectin yields at lower temperatures and shorter extraction times than CHE from grapefruit peel.…”
supporting
confidence: 86%
“…Regarding the in-depth description of specific experimental designs, models, and details concerning the statistics involved in using these tools, interested readers are referred to the fundamental literature on the subject. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]27 The last part of the experimental design involves transforming the data obtained into information and their analysis. The model must be examined to determine if it shows good predictability; this means that it must adequately represent the response function in the experimental domain.…”
Section: Design Of Experimentsmentioning
confidence: 99%
“…Regarding the in-depth description of specific experimental designs, models, and details concerning the statistics involved in using these tools, interested readers are referred to the fundamental literature on the subject. 5–21,27…”
Section: Design Of Experimentsmentioning
confidence: 99%
See 2 more Smart Citations